Analysis of Sodium Benzoate Contents in Beverages Non-BPOM Packaged Fruit Juice Using UV-Vis Spectrophotometry Method - Siti Rahmah Kurnia Ramdan; Syifa Amalia (Mukhtabar Journal of Medical Laboratory Technology, 2025)
Background & Objective: The rapid growth of the beverage industry in Indonesia has led to an increasing circulation of various soft drink products in society, including packaged fruit juice beverages produced by Micro, Small, and Medium Enterprises (MSMEs). These products often contain additional ingredients, particularly preservatives such as sodium benzoate. However, some manufacturers do not provide clear information regarding the concentration of these additives on product labels. The uncontrolled and unmonitored use of food additives may pose potential health risks, especially if the preservatives exhibit carcinogenic properties. This study aims to analyze the levels of sodium benzoate in packaged fruit juice drinks available on the market. The absence of sodium benzoate in the tested samples would indicate that the products are free from synthetic preservatives and therefore safe for consumption. Method: This study employed a descriptive-analytical design to determine the concentration of sodium benzoate in non-BPOM registered packaged fruit juice beverages. Quantitative analysis of sodium benzoate was performed using UV-Vis spectrophotometry. The population consisted of non-BPOM packaged fruit juice beverages available in local markets and retail outlets. Samples were collected using purposive sampling, based on product availability and labeling that did not specify preservative content. Result: The qualitative analysis using 5% FeCl3 reagent indicated positive results for the presence of sodium benzoate in both sample A and sample B. Furthermore, quantitative analysis revealed that the sodium benzoate concentrations in sample A and sample B were each 40 mg/kg (0.004%).   Conclusion: The findings of this study confirmed the presence of sodium benzoate in both non-BPOM packaged fruit juice samples. These levels were relatively low and remained within acceptable safety limits established by international food safety standards, indicating that the analyzed products are safe for consumption with respect to sodium benzoate content.